Implementasi Presensi Online untuk Meningkatkan Disiplin Pegawai di Badan Pendapatan Daerah (BAPENDA) Provinsi Bali - I Made Angga Dewantara Giri Putra; Ni Putu Anik Prabawati; Ida Ayu Githa Girindra (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the implementation of online attendance systems in enhancing employee discipline at the Bali Province Regional Revenue Agency. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and analyzed using George C. Edward III’s implementation theory, which encompasses four key indicators: communication, resources, disposition, and bureaucratic structure. The findings reveal that communication has been effective, characterized by clear and consistent information delivery, thereby reducing employee resistance. While human and financial resources are adequate, the limited availability of supporting facilities hinders optimal implementation. In terms of disposition, employees demonstrate strong commitment and integrity in utilizing the attendance application. The bureaucratic structure has also been appropriately followed, aligning with the usage guidelines set by the Bali Province Office of Communication, Informatics, and Statistics. The study recommends improvements such as enhancing internet infrastructure, increasing supporting facilities, and providing printed user manuals to optimize the implementation of the online attendance system.